2024
DOI: 10.1002/imt2.181
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus GG triggers intestinal epithelium injury in zebrafish revealing host dependent beneficial effects

Zhen Zhang,
Hong‐Ling Zhang,
Da‐Hai Yang
et al.

Abstract: Lactobacillus rhamnosus GG (LGG), the well‐characterized human‐derived probiotic strain, possesses excellent properties in the maintenance of intestinal homeostasis, immunoregulation and defense against gastrointestinal pathogens in mammals. Here, we demonstrate that the SpaC pilin of LGG causes intestinal epithelium injury by inducing cell pyroptosis and gut microbial dysbiosis in zebrafish. Dietary SpaC activates Caspase‐3−GSDMEa pathways in the intestinal epithelium, promotes intestinal pyroptosis and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…For this reason, researchers have begun to pay more attention to host-associated probiotics and their application within aquaculture in recent years [18]. Zhang et al reported on the safety issues when using probiotics obtained from other species in aquaculture, and suggested developing probiotic strains specific to each species rather than directly extending probiotic strains isolated from one species to others [19]. In our previous study, a Bacillus subtilis strain RT-BS07 was isolated from the gut of healthy juvenile rainbow trout.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, researchers have begun to pay more attention to host-associated probiotics and their application within aquaculture in recent years [18]. Zhang et al reported on the safety issues when using probiotics obtained from other species in aquaculture, and suggested developing probiotic strains specific to each species rather than directly extending probiotic strains isolated from one species to others [19]. In our previous study, a Bacillus subtilis strain RT-BS07 was isolated from the gut of healthy juvenile rainbow trout.…”
Section: Introductionmentioning
confidence: 99%